2010
DOI: 10.1007/s00415-010-5691-4
|View full text |Cite
|
Sign up to set email alerts
|

Unusual association of seronegative, nonparaneoplastic limbic encephalitis and relapsing polychondritis in a patient with history of thymectomy for myasthenia: a case study

Abstract: Sirs,Limbic encephalitis (LE) associated with other autoimmune disorders is relatively rare. There is an evidence of LE with relapsing polychondritis [1,2] or Sjogren's syndrome [3], and also with myasthenia gravis [6]. We present a case of LE with an unusual association of different autoimmune conditions.A 73-year-old man developed headache and fever over 2 weeks and a transitory loss of consciousness. His wife reported episodes of confusion over the previous 2 months.He had a medical history of seropositive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Although CNS involvement due to vasculitis is rare, RP has been reported to be associated with aseptic meningitis, meningoencephalitis, encephalitis, and ischemic stroke (3). To our knowledge, there have been 18 cases of RP-associated meningoencephalitis and encephalitis demonstrated clinically and on neuroimaging in the English literature (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The clinical features of the previously reported cases and the present case are summarized in Table. Among these cases, the age of onset was between 29 and 73 years (mean, 55 years).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although CNS involvement due to vasculitis is rare, RP has been reported to be associated with aseptic meningitis, meningoencephalitis, encephalitis, and ischemic stroke (3). To our knowledge, there have been 18 cases of RP-associated meningoencephalitis and encephalitis demonstrated clinically and on neuroimaging in the English literature (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The clinical features of the previously reported cases and the present case are summarized in Table. Among these cases, the age of onset was between 29 and 73 years (mean, 55 years).…”
Section: Discussionmentioning
confidence: 76%
“…Although perivascular cuffing around the meningeal and intracerebral vessels was observed with an increased vascular wall thickness, these histological features were not specific for vasculitis (7). Brain autopsies performed in three cases showed neuronal loss and gliosis in the hippocampus with leptomeningeal lymphocytic infiltrates (8), non-specific meningoencephalitis without evidence of vasculitis (12) and non-specific subacute and chronic inflammation of the meninges and both white and grey matter spreading cortically (18). Although vasculitis is assumed to be the cause of CNS involvement in patients with RP (16), the above-mentioned observations do not support this assumption.…”
Section: Discussionmentioning
confidence: 98%
“…Stewart et al (13) reported extensive cerebral and systemic vasculitis to be the cause of CNS involvement in patient with RP. In contrast, other authors have reported inflammatory changes not specific to vessels in patients presenting with limbic encephalitis or meningoencephalitis associated RP (7,(14)(15)(16)(17). In these autopsy cases, diffuse vasculitis and/or perivascular infiltration were observed, with gliosis in the leptomeninges and brain parenchyma of the limbic area and basal ganglia, etc.…”
Section: Discussionmentioning
confidence: 41%
“…The term seronegative autoimmune encephalitis has been used to describe a subgroup of autoimmune encephalitis cases with negative serologic tests for autoantibodies [2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Seronegative autoimmune encephalitis is a subcategory of autoimmune encephalitis diagnosed when autoimmune antibodies are not detected in cerebrospinal fluid (CSF) or serum [2][3]. The possible reasons for the absence of antibodies, as stated by Najjar et al, include declining serum antibodies and the existence of unidentified antibodies which are yet to be discovered [2].…”
Section: Introductionmentioning
confidence: 99%